(3eG GNJjQ ef GdoefJMd ef GdOQI GdNWjQI aj TYQGAs - (3GdMSf Hf Ydj Hf efLH GdUjQajs; (3Ydj Hf LYaQ Hf Ydj GdSYOj, CHh GdbGSe, GdeYQha H GHf GdbWGY,J (B515 (3g` s
(3ChdgG (B:s
(3YgOj HHhS QHGc hgh fYje CjGe CfJ Ydi GdMSGf cQje s
(3BNQgG (B:s
(3EPG fMf RQfG bHQg jcGKQgG CaVGdg haVGFdg s
(3Vef eLehY s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B269 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B52s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B363 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs